(untitled) (Research, Society and Development, 2020)
Aims: Analyze the social representations of cancer for adult oncological patients with clinical and surgical cancer in a hospital and to identify the contents that are part of the social representations. Method: Qualitative study, supported by the Theory of Social Representations. Thirty people hospitalized for clinical and/or surgical cancer treatment were interviewed at a reference institution specialized in cancer treatment in the city of Rio de Janeiro, Brazil. Results: The group is mostly composed of men (69.3%), with elementary education (57.6%), who live outside the municipality of Rio de Janeiro (56.7%), aged over or equal to 60 years (50.4%). The social representation of cancer showed the waiting processes and complications of surgical treatment, the impact of the diagnosis, the changes resulting from this new health condition, in addition to the support in religiosity, spirituality, and social networks. Conclusions: Understanding the need to improve the care based on humanization offered to people who have cancer, the study observed that those patients need to take care of issues beyond the presented pathology, as a way to make themselves comfort, in order to reduce the negative feelings about this pathology.